Identificação, análise e validação das variáveis ESG essenciais com a proposição de uma estrutura teórico-prática única - Dias, Fábio Martins (2025)
The growing importance of environmental, social, and governance (ESG) criteria reflects a transformation in organizational evaluation and management, essential for organizational performance, preservation, and reputation. Stakeholder pressure, combined with evidence that adherence to these criteria can result in competitive advantages, has driven the prominence of ESG. However, one of the main challenges encountered is the wide variety of variables used by rating agencies, which can cause inconsistencies and uncertainties that hinder comparison between organizations and sectors. With this gap identified, this thesis addresses the question of what essential ESG variables can be used to ensure standardization of ESG performance assessments for organizations, considering different sectors and best practices. By identifying the essential ESG variables, a theoretical-practical framework was developed to enable the standardization of ESG assessments. A total of 579 variables used by the six mains global ESG rating agencies were cataloged. These variables were analyzed using Natural Language Processing (NLP) tools and ESG Expert Analysis, identifying 49 essential variables, which were subjected to market validation to ensure their application in real contexts and to guarantee they are not only theoretically sound. The results indicate that a large number of variables used by rating agencies have the same essence, with many being used to measure similar ESG factors. The research also concludes that identifying the essential ESG variables is crucial for proposing a viable theoretical-practical framework necessary for the development of ESG standards and parameters. The convergence of these variables into an integrated framework provides a basis for creating standards that can be applicable across various sectors, allowing for comparability and consistency in assessing corporate responsibility. Moreover, this approach facilitates the implementation of sustainable and responsible practices, aligning business activities with stakeholder expectations.